ROLE OF COMMUNICATION TOOLS IN THE PROMOTION OF MUSIC: संगीत के प्रचार-प्रसार में संचार साधनों की भूमिका - Khare, Mrs. Asha (International Journal of Research -GRANTHAALAYAH, 2015)
Hegel, a well-known scholar of Jammani, has placed music in the category of love arts. Indian music has been called the essence of all four languages. Music has been worshiped extensively in India and has been worshiped as Veena Vavadani. Sa vidya or liberation is music. In the divine period, the reins of music were in the hands of Brahmins. In this period, music flourished in religious atmosphere. Samudragupta was self-effacing. In this period, music began to develop in Rajashraya. Classical and folk music was also promoted. Kaval Das and Bhasa, the great poet and playwright of Sanskrit, wrote important texts in this period. The Rajputs were ruled after the Gupta period. Indian music, which was embedded in the thread of unity, began to be divided into two streams, the music of North India and the music of South India. Important texts of music were written. In the Muvassalam era, Sharangadee wrote a famous book of music called Sangeet Ratnakara. During this period, Amir Khusro brought a new verse in the field of music. The origins of the plants became popular for singing songs and singing ghazali. Bhagakat music was emphasized during the Mughal period. Dhrupad Dhamar singing was popular. The reign of Akbar in the Mughal period has been called the era of music. During this period, musicians and artists enjoyed royalty, and art greatly developed.